To investigate the effect of neck-shaft angle in surgical hip dislocation combined with femoral neck rotational osteotomy in the treatment of osteonecrosis of the femoral head and to combine with finite element analysis - Jiahao, Sun; Bowen, Ma; Chiyu, Zhang; Tianwei, Xia; Jirong, Shen; Chao, Zhang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe Neck-shaft Angle (NSA) is a reliable predictor of the outcome of internal fixation for femoral neck fractures. Surgical Hip Dislocation Combined with Femoral Neck Rotational Osteotomy (SHD-FNRO) is an effective surgical method for treating femoral head necrosis. However, the potential role of NSA in predicting the outcomes of hip preservation after SHD-FNRO has not been explored.ObjectiveThis study aims to investigate the value of NSA in predicting the outcomes of hip preservation after SHD-FNRO by comparing the results among different patients with osteonecrosis of the femoral head (ONFH) who were treated with SHD-FNRO.MethodsWe retrospectively analyzed clinical data from 33 patients (33 hips) who underwent SHD-FNRO at our hospital between January 2017 and December 2021. Based on the outcome of hip preservation, patients were divided into two groups: group A (successful hip preservation) and group B (failed hip preservation). Statistical analysis was performed to evaluate any differences between these groups. Additionally, three-dimensional models with varying NSA values were created to analyze changes in maximum displacement and stress on the osteotomy surface.ResultsDuring a mean follow-up period of approximately 40 months, successful hip preservation was achieved in 26 patients while 7 patients experienced failure. There was a statistically significant difference in NSA between these two groups (P < 0.05). Biomechanical analysis demonstrated a close relationship between NSA and postoperative biomechanical changes.ConclusionThe size of NSA is closely associated with the success rate of hip preservation when treating osteonecrosis of the femoral head using SHD-FNRO. Therefore, careful attention should be given to selecting an appropriate osteotomy surface that can adjust NSA size effectively, thus achieving better outcomes for hip preservation.